Perspective of MBBS students of a government medical college on various aspects of online medical education: A cross-sectional questionnaire-based survey - Ghosh, Koushik; Das, Arijit; Samui, Bikashendu; Das, Debalina (Asian Journal of Medical Sciences, 2023)
Background: The COVID-19 pandemic and its accompanying lockdown measures adversely affected institution-based education system including medical education. Internet-based online teaching emerged as the only alternative mode of continuing medical education during those times. The situation was novel to the medical institutions, the faculties, as well as the students and involved coordinated effort from all stakeholders for an efficient outcome to the ritual of compulsory online medical education. Aims and Objectives: The study was planned to obtain the perspective and point of view to various aspects of online teaching from of the MBBS students. Materials and Methods: A cross-sectional online survey was conducted through a questionnaire using Google-Forms on MBBS students of Raiganj Government Medical College, Raiganj, from August 1, 2022 for a period of 1 week after obtaining necessary ethical clearance. Results: A total of 174 students responded out of 202. Majority of the respondents (81.3%) said that it was their first experience of online teaching. Most attended 2–3 h of online classes daily and did not want it to be more than that either. Somnolence during class was cited as the most common physical difficulty, while poor network connectivity was the biggest logistic problem. Live lecture was the most preferred mode of online teaching and personal email interaction with the concerned faculties was the most preferred mode for doubt clearing. Most students found online classes inferior than offline classes with respect to opportunity to interact with teachers, class ambience, ability to sustain attention, demonstration of practical skills, and peer-interaction. Conclusion: Online medical education, in spite of all its present drawbacks and demerits, can be used as a tool to provide medical education alongside offline mode after making necessary innovations and modifications by analyzing student as well as faculty feedback.